1997
DOI: 10.1002/(sici)1520-6300(1997)9:1<1::aid-ajhb1>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Frequencies of HLA-A and HLA-B alleles in a Mexico City mestizo sample

Abstract: The aim of the present study was to evaluate the frequency of HLA‐A and HLA‐B antigens in a sample of the Mexico City Mestizo population. Previous similar studies were done by other authors in nonrelated individuals, while the present investigation was performed in families (parents and offspring), and therefore, a more accurate estimate of gene and haplotype frequencies was obtained. The predominant antigens in descending order are A2, A24, and A28 at the A locus, whereas B39 and B35 are at the B locus, all w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…and a diagnosis according to Laurén's classification of gastric adenocarcinoma was established. Mestizo Mexican (ie, descendants of the mixture of the autochthonous population with other ethnic groups [22]) patients, with at least 1 well-preserved paraffin block in the surgical pathology files and a morphologic diagnosis of intestinal poorly differentiated, mixed poorly differentiated, or diffuse adenocarcinoma (G3) in which TNM [3] criteria could be reproduced and with gastrectomy as the main treatment, were included. In addition, a series of consecutive endoscopic biopsies from the same institution (1980)(1981)(1982)(1983)(1984)(1985)(1986) with the diagnosis of diffuse or intestinal adenocarcinoma (G3) in patients nonselected for surgical treatment were also included to counterbalance the selection bias of surgery.…”
Section: Patient Selectionmentioning
confidence: 99%
“…and a diagnosis according to Laurén's classification of gastric adenocarcinoma was established. Mestizo Mexican (ie, descendants of the mixture of the autochthonous population with other ethnic groups [22]) patients, with at least 1 well-preserved paraffin block in the surgical pathology files and a morphologic diagnosis of intestinal poorly differentiated, mixed poorly differentiated, or diffuse adenocarcinoma (G3) in which TNM [3] criteria could be reproduced and with gastrectomy as the main treatment, were included. In addition, a series of consecutive endoscopic biopsies from the same institution (1980)(1981)(1982)(1983)(1984)(1985)(1986) with the diagnosis of diffuse or intestinal adenocarcinoma (G3) in patients nonselected for surgical treatment were also included to counterbalance the selection bias of surgery.…”
Section: Patient Selectionmentioning
confidence: 99%
“…Interestingly in our study, we detected seven patients with B52 and/or B39 alleles, and the other patients presented the B15, B40 and B44 alleles. HLA-B15 and HLA-B40 alleles show a very high frequency in Mexican population and B44 allele is from Caucasian origin with low frequency in Mexican population, apparently acquired by admixture with Caucasian populations [21]. When we analyzed the sequences of these alleles, in spite of its high frequency in the general population, the majority of them showed subtypes that were not common.…”
Section: Discussionmentioning
confidence: 75%
“…In Mestizos with TD who were born in Mexico City, HLA-B39 occurred frequently. 13 In terms of the relationship between UC and the HLA haplotype, Roussomoustakaki et al 14 reported an increase of DRB1*0103 in UC patients, and this association was greatest in patients with extensive disease. This tendency has been observed in European non-Jewish populations.…”
Section: Discussionmentioning
confidence: 95%